2021
DOI: 10.2152/jmi.68.105
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of presepsin / creatinine ratio as a new index that corrects for renal function

Abstract: Background : Presepsin (P-SEP) is a highly specific sepsis marker, and its fluctuation with respect to advanced renal impairment or sample agitation has not been fully investigated. We evaluated several renal function-corrected P-SEP indices to establish a simple index and its reference range. Methods : Blood samples for P-SEP measurement were collected with minimal agitation. P-SEP levels were measured using the rapid automated immunoanalyzer "PATHFAST." This study included 85 chronic kidney disease (CKD) pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…Based on its molecular weight, it is assumed that presepsin is reabsorbed and catabolised within proximal tubular cells after being filtered by the glomerulus. As a result, any condition that impairs renal filtration or tubular function could impact blood presepsin concentration and raise its plasmatic levels 20 …”
Section: Discussionmentioning
confidence: 99%
“…Based on its molecular weight, it is assumed that presepsin is reabsorbed and catabolised within proximal tubular cells after being filtered by the glomerulus. As a result, any condition that impairs renal filtration or tubular function could impact blood presepsin concentration and raise its plasmatic levels 20 …”
Section: Discussionmentioning
confidence: 99%
“…Sep-3 has been proposed as a new diagnostic criterion for sepsis, and thus future studies on the diagnostic accuracy of Pre based on the Sep-3 criterion are needed. Considering the relationship between Pre and renal function, a recent study reported that the Pre/serum Cr ratio did not depend on the GFR stage, and the reference ratio was 67–263, which was significantly higher in patients with sepsis [ 18 ]. More studies are needed to investigate whether the Pre/Cr ratio or a different cut-off setting for patients with advanced renal impairment is more useful for the diagnosis of sepsis in patients with renal dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…263, which was significantly higher in patients with sepsis [18]. More studies are needed to investigate whether the Pre/Cr ratio or a different cut-off setting for patients with advanced renal impairment is more useful for the diagnosis of sepsis in patients with renal dysfunction.…”
Section: Plos Onementioning
confidence: 96%
“…У пациентов с тяжелой почечной недостаточностью оптимальные пороговые значения пресепсина составляли 500 нг/л (диагностическая чувствительность -89,7%, диагностическая специфичность -59,7%). Таким образом, значения пресепсина были выше в группе пациентов с тяжелой почечной недостаточностью по сравнению с таковыми у здоровых пациентов [28].…”
Section: пресепсинunclassified